AN ANALYSIS OF ENGLISH TEXTBOOK RELEVANCE TO THE 2013 ENGLISH CURRICULUM - Yokie Prasetya Dharma; Thomas Joni Verawanto Aristo (Journal of English Educational Study (JEES), 2018)
Textbook is the heart of teaching and is also a crucial part in the curriculum. However, it is often found out that the materials of a textbook do not represent well the goal targeted in the curriculum.Given this thinking, then this study is aimed at finding out the relevancies of the materials found in the textbook with the 2013 curriculum materials. Utilizing qualitative research through interview with the teacher done on April 4th, 2017 to find teacher’s rationale using the textbook and the document checklist to find the relevance of the textbook to the 2013 curriculum, this study found out that the English textbook used had been relatively relevant to the 2013 curriculum with few lack of relevance to the 2013 curriculum. Therefore, it is expected that theteacher can complete such few lack with other materials to achieve the goal targeted in the 2013 curriculum as well.Keywords: Textbook, 2013 curriculum